Heutagogical Approach in Play and Games Courses of Early Childhood in Online Learning - Mursyida; Kholida Munasti; Elvi Mardiana (JOYCED: Journal of Early Childhood Education, 2023)
This study aims to describe the use of hetagogy approaches in early childhood play and play courses during the online learning phase in the Early Childhood Islamic Education and Research Program at Sultan Taha Jambi National Islamic University. Because of the COVID-19 pandemic, the lecture process will be conducted via distance learning. This is often called online education. However, the effect of absorbing teaching materials is reduced. Due to the lack of active interaction and being limited to online screens, different learning approaches, such as the hetagogy approach, are being used to re-streamline learning in the online classroom. Has been introduced. This study uses Miles and Huberman's interactive model as a case study of data analysis techniques. Data collection from interviews with 26 students and one lecturer. This research shows that students with a bullish approach encourage more active faculty-student interaction and collaboration, exchange ideas, critical thinking, independence, and successful communication research projects. By doing so, we demonstrate that we are having a positive impact.